Tales from Shakespeare - Charles (Penguin Readers, 2008)
This book includes stories based on seven of Shakespeare's greatest plays. We meet many of Shakespeare's most famous characters - magical Prospero; Puck, the badly-behaved fairy; evil Macbeth; Shylock, the greedy moneylender, and many more. This is a wonderful first step on the journey into the world of Shakespeare.